2023
DOI: 10.1111/ijfs.16510
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of Moringa oleifera supplemented cookies and their ameliorative effect on the lipid profile of hyperlipidaemic patients

Abstract: SummaryRaised cholesterol levels can alleviate the risk of cardiovascular diseases and stroke and are responsible for one‐third of all ischemic heart diseases worldwide. Moringa oleifera (MO) plant has gained nutraceutical prominence; therefore, its lipid‐lowering potential was investigated by its incorporation (leaves MOL, seeds MOS and leaves + seeds MOLS) into cookies. These cookies were then analysed for nutritional, physicochemical and clinical properties. The sensory properties received overall higher ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The addition of MOLP to wheat flour possibly increased the viscosity of the dough, thereby increasing its hardness after baking. Previous studies also found an increase in cookie hardness following the addition of MOLP to wheat flour using instrumental methods [ 17 , 55 ] and subjective sensory analysis [ 56 ]. Another plausible reason for the increase in hardness is the higher level of protein in the Moringa-enriched cookies ( Table 2 ) as explained later ( Section 3.5 ).…”
Section: Resultsmentioning
confidence: 86%
“…The addition of MOLP to wheat flour possibly increased the viscosity of the dough, thereby increasing its hardness after baking. Previous studies also found an increase in cookie hardness following the addition of MOLP to wheat flour using instrumental methods [ 17 , 55 ] and subjective sensory analysis [ 56 ]. Another plausible reason for the increase in hardness is the higher level of protein in the Moringa-enriched cookies ( Table 2 ) as explained later ( Section 3.5 ).…”
Section: Resultsmentioning
confidence: 86%